Interpreting in Ireland's Asylum Process - Kiboua, Hassina (School of Religions, Peace Studies and Theology, Irish School of Ecumenics, Trinity College Dublin, 2022)
Asylum applicants fleeing persecution and seeking hospitality do not usually speak the language of the host-country. They express themselves through an interpreter, who mediates between asylum applicants and the examining institutions. In this, interpreters find themselves dealing with a variety of contexts including, a wide cultural gap, power imbalance, and the tension between the applicant’s universal human right to seek hospitality and the host-county’s right to self-determination along with the politics of exclusion exercised towards the outsider asylum applicant. Building on the premise that interpreters are vital for the asylum process to function and for asylum seekers to establish their claim and access due process, this research aims to explore interpreting-related issues in the Irish asylum process; to look at the impact that interpreting might have on the asylum application and the asylum process. In the absence of a national regulation, accredited qualifications, and training for interpreters in Ireland, this research asks whether the current provision of asylum interpretation in Ireland promotes the realisation of universal rights or contribute to a politics of exclusion. A triangulation of five research methods is used to explore the role and quality of interpreting in the Irish asylum settings. Starting by an observational method of asylum consultations, complemented by semi-structured interviews with key participants in the setting, including interpreters, legal representatives, an interpreters’ trainer, and Tribunal Members. The third method involved the analysis of asylum questionnaires in the original language and English, followed by legal analysis asylum High Court cases. The final method involved a review of existing reports, publications, studies, and articles in the Irish context and a comparison to other practices globally. Using a theoretical framework based on Benhabib’s “the Right of Others”, in which the focus is on the tension between the universal and the local; and the inherent politics of exclusion in the local asylum policies; this thesis finds little evidence that the implementation of interpreting services and the right to an interpreter is affected by the politics of exclusion. However, the tension between the universal and the local is in evidence as the wide discretion of asylum institutions and officials in implementing interpreting services and their personal attitude towards language and interpreting is reflected in the realization of the right to an interpreter in practice. Interpreting services and access to justice are therefore affected by the discretion of asylum institutions and by the language approach of Irish asylum officials including judges. Overall, predominant, and concerns emerge from the confusion about the role of interpreters and the quality and reliability of services being provided by these interpreters, which go down to the lack of regularization, training, and a national protocol.
Keywords: Community Interpreting; Asylum; Inclusion; Exclusion; Universal Rights; Local Practices